COMPARATIVE ANALYSIS OF ETHNIC POLITICS IN KAZAKHSTAN AND GERMANY - Atantayeva, B.; Adikeeva, A. (European Scientific Journal, ESJ, 2014)
Thу article describes one of the modern problems – political condition of international relations, relations between nations and inter-ethnical consent. The authors analyze the experience of Kazakhstan and Germany in ethnic politics, explore the importance of these issues in the world today.